Utilization of Quercetin Flavonoid Compounds in Red Onion (Allium cepa L.) as Inhibitor of Spike Sars-CoV-2 Protein against ACE2 Receptors - Syifa Zahara Kultsum Azmi; Sunarno Sunarno; Sinta Aulia Rahmah; Melisa Andriani; Azlya Reza Lailul Farobi; Luke Nur Ahlina (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
The world is facing the challenge of the COVID-19 disease, which is now stated as a pandemic. Inside the host cell, spike envelope protein (spike) of SARS-CoV-2 interact with the Angiotensin-converting Enzyme 2 (ACE2) receptor. It can be inhibited by bioactive compounds such as flavonoids which have anti-viral and broad pharmacological effect. This study aimed to determine the spike protein inhibitory activity by quercetin against the ACE2 receptor using the molecular docking method. This study focused on the inhibitory of the penetration activity of s proteins in ACE2 by utilizing natural material compounds that have the potential to be used as anti-SARS-CoV-2 drug development agents. The flavonoid compound quercetin was extracted by the maceration method. The quantitative analysis was carried out using a UV-Vis spectrophotometer to prove the presence of quercetin content. Molecular docking simulations were carried out to look for the binding affinity between the spike protein and quercetin. Docking was carried out using the Autodock, PyRx, and visualization using Discovery Studio. Indicators that prove that quercetin forms binding affinity and protein complexes with spikes are the Vina Score and RMSD. It is also supported by ADME analysis and conformity to Lipinski's rules of five. That matter becomes a success indicator of the spike activity inhibition by quercetin, which makes it possible to be used as an anti-SARS-CoV-2 drug development agent. The novelty from this study is molecular docking method that used to show that quercetin in red onion had inhibitory activity on the penetration process of protein spike in SARS-CoV-2. Results obtained from this study can be used as a recommendation for advanced research in invitro and invivo studies as a drug which has potential to inhibit protein spike of SARS-CoV-2.